Prevalensi Cemaran Bakteri Indikator Sanitasi dan Patogen pada Daging Ayam dan Produk Olahannya di Indonesia: Sistematika Review dan Meta-Analisis - Sri Madiarti Sipayung; Winiati P. Rahayu; Siti Nurjanah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2023)
Chicken meat, a staple of the Indonesian diet, undergoes extensive examination for contamination across diverse regions, yielding different findings. Using a comprehensive meta-analysis approach by combining previous researchees, making the results are widely applicable and understandable. This research aimed to obtain prevalence of bacterial contamination and pathogenic agents in both raw chicken meat and processed chicken products in Indonesia. The investigation occured in two sequential phases: first, a systematic review, including literature retrieval from databases like Google Scholar, Cross Ref, Pro Quest, PubMed, and Science Direct, followed by literature screening and data extraction. Then, in the second stage was conducted a meta-analysis. Effect size measurements, primarily the proportion/prevalence of bacterial contamination, are calculated using the random-effects model via the DerSimonian–Laird method. Analysis of 44 studies from 25 carefully selected literature sources shows that the prevalence of bacterial contami-nation in Indonesian chicken meat and its processed derivatives is 32.8% (95% CI: 21.6-44.1, I2 = 99.49%). To address the noticeable heterogeneity, sub-group meta-analyses was performed, which was categorized by sample type, the specific contaminating bacteria, and the sampling location. The sub-group meta-analysis based on sample type highlights processed chicken meat as having the highest prevalence at 47.8%. When broken down by bacterial type, contamination rates reveal E. coli (45.3%), Salmonella sp. (30.6%), Campylo-bacter sp. (20%), and L. monocytogenes (15.7%) as significantly influencing the prevalence of bacterial contamination in Indonesian samples. Geographically, traditional markets emerge as the primary source of bacteria-contaminated samples, with a prevalence rate of 31.2%.